A comparative study on journalistic processes and practices at ABS-CBN's TV Patrol and Patrol ng Pilipino - Melgarejo, Karmela Marae R.
In a media landscape disrupted by platform shifts and algorithmic audiences, Philippine newsrooms have begun reinventing themselves through digital innovation to continue their journalistic mission. Using mixed-method approach, this study compared the journalistic routines of ABS-CBN reporters in the traditional newscast TV Patrol with the vertical video platform Patrol ng Pilipino, exploring how they adapt to evolving platforms while upholding journalistic ethics. The researcher analyzed 181 videos from top reporters who contribute to Patrol ng Pilipino along with semi-structured interviews. Guided by Csikszentmihalyi’s Systems Model of Creativity, the study examined how journalistic routines, ethics, and storytelling techniques shift between traditional and digital formats. Findings revealed that TV Patrol maintains a structured and rigid process, with complete news organizational structure. In contrast, Patrol ng Pilipino embraces a personality-driven, where reporters singlehandedly shoot, script, and edit stories independently, often using humor, plain language, and explainers to engage social media audiences. Despite this stylistic shift, core journalistic values such as accuracy, balance, and integrity remain intact. Interviewed reporters emphasized the technical challenges in editing videos. Nevertheless, they recognized the need for media organizations to innovate without compromising ethical standards in an increasingly fragmented and fast-paced news ecosystem.